ANALISIS KETERBUKAAN PENERIMAAN DAN PENGELUARAN KAS BAGI SUSTAINABILITY BPR BANK JOGJA SEBAGAI WUJUD ANTISIPASI KETIDAK PASTIAN AKIBAT PANDEMI COVID-19 - Arianti, Devi Sella (LP2M Institut Teknologi dan Bisnis Asia Malang, 2021)
Bank BPR Jogja is considered a grassroots entity that has an obligation to contribute to providing stimulus during the pandemic and to drive the welfare of its members in times of uncertain economic growth due to the Covid-19 pandemic. Preparation of financial reports has an important factor, namely the openness of cash receipts and disbursements which will be presented through research by measuring 6 aspects of the application of internal control in the cash receipt and disbursement cycle according to the COSO framework in BPR Bank Jogja, namely 1) accountability, 2) control environment, 3) assessment risk, 4) control activities, 5) information and communication, and 6) monitoring. This study aims to determine the analysis of the openness of cash receipts and payments and then identify the weaknesses and strengths that have been implemented through the measurement of significance together. This study uses a quantitative research method using a fact approach and analysis of its effects directly at the BPR Bank Jogja unit. The results of the study concluded that the analysis of the openness of cash receipts and disbursements at Bank BPR Jogja has gone well, in line with the strengths and weaknesses identified.